Antimicrobial efficacy of Portland cement and Mineral Trioxide Aggregate against Enterococcus faecalis and Candida albicans (Research, Society and Development, 2022)
The objective of this study was to review the available literature on the characteristics of Portland cement and Mineral Trioxide Aggregate with emphasis on their antimicrobial activity against the most prevalent pathogens in endodontic reinfection. Portland cements and Mineral Trioxide Aggregate, both based on calcium silicate, are used in various areas of dental therapy, especially in endodontic procedures, as they stimulate biomineralization mechanisms. They are in contact with dental structures, bone and connective tissue, therefore, they face an additional challenge regarding their antibacterial and antifungal properties against various microorganisms such as Enterococcus faecalis and Candida albicans; which are resistant to conventional disinfection procedures, especially due to their ability to form biofilms and are associated with root canal treatment failures. In the review carried out, it was shown that in general Portland cement and Mineral Trioxide Aggregate have similar antimicrobial properties and present antimicrobial activity against Enterococcus faecalis and Candida albicans.